Stability analysis in buckwheats (Fagopyrum species) - Joshi, B D; Rana, J C (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the rainy (kharif) season of 1988-92 to study stability analysis in 3 genotypes of sweetbuckwheat (Fagopyrum esculentum Moench) and 10 genotypes of bitter buckwheat [F. tataricum (L.) Gaerun]. The varietiesperformed differently during different years and showed significant genotype X environment interactions for plant height,leaf length, branches/plant and seed yield. ’Himpriya’ and ’IC 18889-’ were found stable for branches/plant, seed weight andseed yield in 5 years. Though ’Kulu Gangri I’, ’IC 13376" ’IC 18869’ and ’VHC 26’ showed high mean performance, were foundunstable either due to linear or nonÂ·linear genotype x environment interaction. Based on their highÂ·mean performance thesevarieties may be tested further in different locations in different years to establish their superiority and stability.